Evaluation of the Impact of the Colombian Scientific Productivity on the Fulfillment of the Sustainable Development Goals - OSTOS-ORTIZ, Olga Lucía; RENTERÍA-RAMOS, Rafael; CALA-VITERY, Favio (Journal of Environmental Management and Tourism, 2022)
This research presents the development of an instrument for the evaluation of the contributions of scientific production in Colombia to the development of the main needs of the Sustainable Development Goals (SDG) throughout the country. A data set of national and international science and technology repositories was configured, including those recognized for hosting products highly related to the topics required by the SDGs. Afterward, a topic model was built, in which for each of the sources considered in each SDG, the importance of the number of topics or categories and the distribution of the concepts in each of them was evaluated based on indicators such as perplexity and coherence. Among the most important results, the synchronization of the scientific products related to the objectives “ Fin de la pobreza ”, “ Cero Hambre ” and “ Salud y Bienestar ” stands out, however, despite this decisive result for the fulfillment of the SDGs, the lack of scientific development throughout the national territory limits the impact of the results for the attainment of the agenda for 2030.